2015
DOI: 10.1055/s-0034-1393076
|View full text |Cite
|
Sign up to set email alerts
|

Development of a device for detecting target specimens from EUS-guided FNA samples

Abstract: Background and study aims: Specimens collected by fine needle are microscopic and contain blood; therefore, the presence of a target specimen within a sample is often difficult to confirm. Although rapid on-site evaluation (ROSE) during endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNA) is beneficial, many health care facilities are unable to apply this technique due to a lack of cytopathologists. The aim of this study was to develop and validate a device that detects the target specimen with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
3
14
0
Order By: Relevance
“…Our data indicate better results, but our findings and those reported by Nguyen et al cannot be compared because of the differences in patient backgrounds and the method by which the specimens were processed [25]. Matsumoto et al showed good agreement with a target sample check illuminator (TSCI) [26]. The TSCI can use the 605-nm wavelength, which may account for differences.…”
Section: Discussionsupporting
confidence: 44%
“…Our data indicate better results, but our findings and those reported by Nguyen et al cannot be compared because of the differences in patient backgrounds and the method by which the specimens were processed [25]. Matsumoto et al showed good agreement with a target sample check illuminator (TSCI) [26]. The TSCI can use the 605-nm wavelength, which may account for differences.…”
Section: Discussionsupporting
confidence: 44%
“…Furthermore, there are still some areas or hospitals where patients cannot receive EUS‐FNA. Although the overall complication rate for EUS‐FNA has been reported as 2% and research to decrease the complication rate has been reported, it is not free from complications. Complications include pain, bleeding, fever, and infection.…”
Section: Introductionmentioning
confidence: 99%
“…Whether tissue sampling could be performed was determined visually by the endoscopist and using the Target Sample check illuminator (TSCI), which we developed and previously reported on its utility. 12 If sample collection was not successful the fi rst time, an additional puncture was performed.…”
Section: Eus/eus-fna Proceduresmentioning
confidence: 99%